New Records of Microfungi and Chromista from Anatolian Peninsula of Turkey - OZASLAN,C. (2018)
ABSTRACT: This article presents new records of fungi and downy mildews in Turkey on different weeds of agrophytocoenosis. These records include Plectosphaerella alismatis (Oudem.) A.J.L. Phillips, Carlucci & M.L. Raimondo (on Alisma plantago-aquatica L.), Pyricularia grisea Sacc. (on Setaria viridis (L.) P. Beauv.), Phakopsora artemisiae Hirats. (on Artemisia dracunculus L.), Puccinia rubefaciens Johanson (on Galium sp.), Ustilago trichophora (Link) Kunze (on Echinochloa crus-galli (L.) P. Beauv.), Peronospora astragalina Syd. (on Astragalus homosus L.) and P. myagri Mayor (on Myagrum perfoliatum L.). Plectosphaerella and Phakopsora as generic level and others as species are new records from Turkey. Description and illustrations of the identified fungi are presented, which all are based on Turkish specimens. The identified fungi could be potential biological control agents; however, detailed studies are needed in this regard.